2019
DOI: 10.21462/ijefl.v4i2.198
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges of Language Learning of the Study-Abroad Students of English Language Department of Islamic Higher Education in Kalimantan

Abstract: The purpose of this study is to uncover: 1) How foreign students believe in learning English at Islamic higher education in Kalimantan, 2) The experience of foreign students in learning English at Islamic higher education in Kalimantan, 3) The challenges of foreign students in learning English at Islamic higher education in Kalimantan. This qualitative phenomenological research was to disclose the phenomenon of the entry of foreign students to Kalimantan. The main participants of the study were foreign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Some participants reported issues related to the food of the host country. This finding supports other studies which revealed food is one of the challenges for international students (Wahyuningsih, 2020;Fauzan & Nadia, 2019;Alsulami, 2018;Tsevi, 2018;Rabia, 2017;Alazzi & Al-Jarrah, 2016). The data finding revealed that sometimes the participants missed their native food and had difficulty adapting to the food of the host country because the food is too spicy for them.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Some participants reported issues related to the food of the host country. This finding supports other studies which revealed food is one of the challenges for international students (Wahyuningsih, 2020;Fauzan & Nadia, 2019;Alsulami, 2018;Tsevi, 2018;Rabia, 2017;Alazzi & Al-Jarrah, 2016). The data finding revealed that sometimes the participants missed their native food and had difficulty adapting to the food of the host country because the food is too spicy for them.…”
Section: Discussionsupporting
confidence: 89%
“…The results showed that international students faced some challenges in their adjustment, such as language, weather, food, education system, way of thinking, and social relation. Furthermore, Fauzan and Nadia (2019) qualitatively investigated the challenges of language learning experienced by international students at Islamic higher education in Kalimantan. They revealed that the international students faced various challenges, such as increasing selfconfidence, mastering learning material, improving English speaking skills, and adapting to the environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Role-play can be offered as a solution for English students or learners who have difficulty mastering English, especially speaking. Teachers can try to deal with problems of anxiety and difficulty in speaking English, such as the findings of Sayuri 23 , Dian et al 24 , Shiauping Tian & Masykur Mahmud 25 , Cucu Sutarsyah 26 , or Umar Fauzan & Nadia 27 where the anxiety can be tried to be resolved by implementing Role-play.…”
Section: IIImentioning
confidence: 99%